(untitled) (ENTHYMEMA, 2017)
Recensiamo l’edizione italiana, curata da Massimo Bonafin, del libro di Eleazar Moiseevič Meletinskij Archetipi letterari. Trad. Laura Sestri. Macerata: eum, 2016. Review of the Italian edition of Eleazar Moiseevič Meletinskij’s book Archetipi letterari, edited by Massimo Bonafin. Translation by Laura Sestri. Macerata: eum, 2016.